1983
DOI: 10.1056/nejm198308253090803
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of B-Cell Activation and Immunoregulation in Patients with the Acquired Immunodeficiency Syndrome

Abstract: We studied B-lymphocyte function in 12 homosexual male patients with the acquired immunodeficiency syndrome, 5 healthy homosexual men, and 12 heterosexual controls. In comparison with the heterosexual controls, the patients were found to have elevated numbers of cells spontaneously secreting immunoglobulin, decreased B-cell proliferative responses to T-cell-independent B-cell mitogens, and qualitatively deficient helper T cells. The hyperactive spontaneous B-cell responses as well as the refractoriness to sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
591
3
9

Year Published

1984
1984
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,510 publications
(627 citation statements)
references
References 15 publications
24
591
3
9
Order By: Relevance
“…Thus the dramatic increase of circulating IgA in HIVinfected subjects is probably related to both a polyclonal activation of B cells, producing mainly the monomeric form IgA1 isotype [23], and a crossing of sIgA from mucosal origin [35]. Our study also demonstrated that the frequency of IgA isotype antibodies to HIV-1 structural proteins was lower in parotid saliva than in serum, but did not decrease during the course of HIV-1 infection.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Thus the dramatic increase of circulating IgA in HIVinfected subjects is probably related to both a polyclonal activation of B cells, producing mainly the monomeric form IgA1 isotype [23], and a crossing of sIgA from mucosal origin [35]. Our study also demonstrated that the frequency of IgA isotype antibodies to HIV-1 structural proteins was lower in parotid saliva than in serum, but did not decrease during the course of HIV-1 infection.…”
supporting
confidence: 55%
“…The horizontal line corresponds to the level of albumin above which parotid saliva was considered to be contaminated by blood. [23,24], having been proposed as a surrogate marker to follow the course of HIV infection [25]. In this study, parotid saliva was used to evaluate the variation of IgA and IgG concentrations at the mucosal level during HIV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, persistent immune activation, which is described as elevated T-lymphocyte turnover and apoptosis; polyclonal B-cell activation; increased NK-cell activation and turnover; and dendritic cell activation, 7,14,15 was found to be a hallmark of HIV infection. In fact, it is well associated with CD4 1 T cell counts and HIV viral loads.…”
Section: Discussionmentioning
confidence: 99%
“…4,82 The broad activation of B lymphocytes in HIV infection is wellcharacterized. [3][4][5][7][8][9] This B cell activation, with the expansion of EBV-infected B cell populations, may be the initial steps in B lineage tumorigenesis and may account for the high frequency of oligoclonal lymphoma observed in these patients. 5 Such a broad lymphocyte activation may predispose to the generation of lymphoma even in the absence of EBV infection.…”
Section: Gammopathy and Plasma Cell Tumors In Aidsmentioning
confidence: 99%
“…[1][2][3][4] Although HIV-infected individuals have deficiencies in CD4-positive T helper cells, and thus might be expected to have problems with B cell activation and immunoglobulin secretion, experimental studies of B lymphocytes in HIV infection have revealed polyclonal B cell activation. 3,5 B cells exposed to HIV in vitro may proliferate 6 or become activated and begin secreting immunoglobulin. 4,7,8 HIV-infected T cells can induce contact-dependent but antigen-independent polyclonal activation of B cells.…”
Section: Introductionmentioning
confidence: 99%